2021
DOI: 10.1002/ange.202113464
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Catalyzed Dearomatization by Intramolecular Hydroalkoxylation/Claisen Rearrangement: Diastereo‐ and Enantioselective Synthesis of Spirolactams

Abstract: Described herein is a novel Brønsted acid catalyzed intramolecular hydroalkoxylation/Claisen rearrangement, allowing the practical and atom‐economic synthesis of a range of valuable spirolactams from readily available ynamides in generally good to excellent yields with excellent diastereoselectivities and broad substrate scope. Importantly, an unexpected dearomatization of nonactivated arenes and heteroaromatic compounds is involved in this tandem sequence. Moreover, an asymmetric version of this tandem cycliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The Beller group suggested that P2 resulted from the simple Brønsted acid-catalyzed etherification of the alkene . Brønsted acids have been exploited to catalyze the hydroalkoxylation reaction of simple alkenes attributed to their ability to electrophilically activate CC double bonds to facilitate the formation of the C–O and C–N bonds. , Moreover, the generally applied methods to accomplish these reactions are those using either transition metal catalysts (such as Pd, Cu, Fe, Pt, and Ti complexes) or main-group metal catalysts. , The most favorable pathway for Brønsted acid or metal catalyzed-hydroalkoxylation includes nucleophile attack and proton transfer in a stepwise or concerted way assisted by a proton-transfer agent present in the solution. , The aforementioned publications also raised the debate on the question of Brønsted acid or palladium-catalyzed hydroalkoxylation reactions taking place in Beller et al’s experimental reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The Beller group suggested that P2 resulted from the simple Brønsted acid-catalyzed etherification of the alkene . Brønsted acids have been exploited to catalyze the hydroalkoxylation reaction of simple alkenes attributed to their ability to electrophilically activate CC double bonds to facilitate the formation of the C–O and C–N bonds. , Moreover, the generally applied methods to accomplish these reactions are those using either transition metal catalysts (such as Pd, Cu, Fe, Pt, and Ti complexes) or main-group metal catalysts. , The most favorable pathway for Brønsted acid or metal catalyzed-hydroalkoxylation includes nucleophile attack and proton transfer in a stepwise or concerted way assisted by a proton-transfer agent present in the solution. , The aforementioned publications also raised the debate on the question of Brønsted acid or palladium-catalyzed hydroalkoxylation reactions taking place in Beller et al’s experimental reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the related catalytic asymmetric transformations were established via a remote control of enantioselectivity. Inspired by these results and by our recent study of the development of ynamide chemistry for heterocycle synthesis [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] , we envisioned that the vinyl cations generated from copper-catalyzed diyne cyclization might be trapped by 1,2,5-oxadiazoles, eventually leading to valuable 1,2,5-oxadiazines via one-carbon homologation (Fig. 1b).…”
mentioning
confidence: 99%
“…According to our initial design (Scheme ), the N -alkynylindole-2-carbinols 1 in the presence of an acid (Brønsted/Lewis) may undergo an intramolecular Z -selective hydroalkoxylation on to the alkyne to form the cyclic enol-ether 2 via a ketenimine like intermediate 3 . This ether 2 , under reaction conditions, might undergo a diastereoselective O – C 1,3-rearrangement to result in the formation of anticipated pyrrolo­[1,2- a ]­indol-3-ones 4 .…”
mentioning
confidence: 99%